PECULIARITIES OF CONSTRUCTION PROFILES OF SECURITY SYSTEMS OF INFORMATION SYSTEMS - Olga V. Lukinova; Andrey V. Pugachev (Открытое образование (Москва), 2016)
Examines the specific issues of building functional and technological profiles of the security systems to ensure the safety of information systems in the paradigm of functional standardization; shows a view of the system of protection based on the model of OSE/RM; studied the composition and structure of the concept of "defense mechanism" for the purpose of profiling third instalment correction representation of the system of protection.